TASPO Makes Hit in Paris - Unknown (Evening News)
The Trinidad All Steel Percussion Orchestra (TASPO) has made a great hit in Paris, where it provided the entertainment for three weeks at the Cafe Medrano, a popular Paris night spot. The French press reported that "the only instruments used by the native Trinidad orchestra members are gasoline and oil drums and the sticks with which they produce so pure, well harmonised notes. The rhythm of this orchestra is generally that of the rhumba and samba"
Keywords: Steel drum (Musical instrument) -- Trinidad and Tobago; Steel band music -- France; Music -- Performance -- France; Steel bands (Music) -- France